2015
DOI: 10.1242/jcs.167643
|View full text |Cite
|
Sign up to set email alerts
|

The adipocyte clock controls brown adipogenesis via TGF-β/BMP signaling pathway

Abstract: The molecular clock is intimately linked to metabolic regulation, and brown adipose tissue plays a key role in energy homeostasis. However, whether the cell-intrinsic clock machinery participates in brown adipocyte development is unknown. Here, we show that Bmal1 (also known as ARNTL), the essential clock transcription activator, inhibits brown adipogenesis to adversely affect brown fat formation and thermogenic capacity. Global ablation of Bmal1 in mice increases brown fat mass and cold tolerance, and adipocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 74 publications
4
56
0
Order By: Relevance
“…However, in this study, Tgf-β1 levels were lower in animals exposed to a short photoperiod, suggesting circadian rhythm disruptions may influence this regulation. In support of this, a recent study showed that BMAL1, an essential clock transcription activator, inhibits brown adipogenesis via direct transcriptional control of key components of the TGF-β pathway, including TGF-β1 [46].…”
Section: Discussionmentioning
confidence: 85%
“…However, in this study, Tgf-β1 levels were lower in animals exposed to a short photoperiod, suggesting circadian rhythm disruptions may influence this regulation. In support of this, a recent study showed that BMAL1, an essential clock transcription activator, inhibits brown adipogenesis via direct transcriptional control of key components of the TGF-β pathway, including TGF-β1 [46].…”
Section: Discussionmentioning
confidence: 85%
“…BMP-8b is also expressed in brown adipose tissue and increases thermogenesis not only locally but also systemically through central nerve systems (Whittle et al 2012). Furthermore, a balance between BMP and TGF-b signaling regulates brown adipogenesis through a regulation by Bmal1, a circadian clock transcription factor (Nam et al 2015). These finding indicate that multiple BMP ligands regulate both white and brown adipocyte differentiation in vivo.…”
Section: Adipogenesis and Fat Tissuesmentioning
confidence: 84%
“…one study reported that regulation of clock genes controlled BMP2 expression in osteoblasts (26). Meanwhile, BMAL1 regulation of TGF-β and BMP signaling in the control of fat adipogenesis has also been reported (27). a recent study showed that BMal1 silencing-induced BMP2 was found in rat uterus endometrium stromal cells (28).…”
Section: Discussionmentioning
confidence: 99%